Measurement of energy efficiency economic-development linkage: A Parametric Method of Stochastic Frontier Analysis (SFA) - Neelma Shamsi; Maryam Ishaq (Dialogue Social Science Review (DSSR), 2025)
The paper examines the correlation between economic development and energy efficiency (EE) in 18 countries in the European Union (EU) in the period between 2012 and 2022. In the analysis, a parametric analysis is used in order to measure EE and estimate efficiency scores by applying a Stochastic Frontier Analysis (SFA). The models were used to estimate separately the electricity and gas consumption in both household and non-household sectors. The study attempts to shed some light on the heterogeneous consequences of development and environmentally oriented technological progress on the national levels of energy efficiency by considering a broad portfolio of economic, environmental, and demographic indicators. The four SFA models were used to estimate efficiency scores of household and non-household electricity and gas consumption. Static models demonstrated moderate efficiency and could not isolate persistent inefficiencies nor transient ones. TRE model by Greene (2005) has found out that the inefficiencies especially in the non-household sector have been mainly structural. The impact of income on energy efficiency is positive, and the low effects of environment spending, innovation indicate policy gaps. Climate variables decrease efficiency with a focus on regional differences. Keywords: Energy efficiency, Economic development, Stochastic Frontier Analysis, European Union (EU)